RELATIONSHIP BETWEEN E-BANKING, CUSTOMER SATISFACTION AND CUSTOMER LOYALTY - M. Elakkiya; Priyadharisini, Mary J (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The goal of this research is to analyse the relational impact between e-banking service quality, customer satisfaction and customer loyalty. Questionnaire was used as the research instrument to evaluate the dimensions of relations and distributed among the e-banking Chennai customers. Using simple random sampling technique, 240 samples were collected from the customers located in Chennai city. For the data analysis, SPSS Software version-28 was used to evaluate to reliability, correlation and difference between the variables. Demographic Analysis, Descriptive Analysis, Correlation, Reliability Analysis and ANOVA were used as the statistical tools. Result of correlation analysis and reliability analysis are lower than the significant value and accept the alternative hypothesis. Through ANOVA difference between the variables were analysed and found that there is no relationship between the variables. This research also suggests the implement high quality in e-banking services and that impact on high customer satisfaction and customer loyalty.